2010
DOI: 10.1161/hypertensionaha.110.151654
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension Is a More Robust Predictor of Cardiovascular Events Than Nighttime Reverse Dipping in Elderly

Abstract: Abstract-Aims of the study were to assess in an elderly population the prevalences of orthostatic hypotension at different times after standing and of nighttime reverse dipping on ambulatory blood pressure monitoring, as well as their interrelationships and relative prognostic power for incident cardiovascular events. The study population consisted of 374 patients (225 women), aged 70.2Ϯ8.5 years, registered in 1 primary care practice and without major cardiovascular events or other comorbidities at baseline. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
2
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 32 publications
3
76
2
15
Order By: Relevance
“…[40][41][42] However, in a recent analysis, this association was no longer significant after adjustment for frailty, suggesting that the latter is more important for survival. 43 …”
Section: Risk Of Cardiovascular Events and Mortalitymentioning
confidence: 91%
See 1 more Smart Citation
“…[40][41][42] However, in a recent analysis, this association was no longer significant after adjustment for frailty, suggesting that the latter is more important for survival. 43 …”
Section: Risk Of Cardiovascular Events and Mortalitymentioning
confidence: 91%
“…79 However, the association of orthostatic hypotension with risk of cardiovascular events was mainly because of the delayed orthostatic BP drop. 42 In conclusion, the bulk of the evidence suggests that, overall, increasing systolic and diastolic BP is associated with increasing cardiovascular risk and mortality. The picture is far less clear, however, in older individuals who are frail, as indicated, for example, by walking speed or comorbidity.…”
Section: Risk Of Functional Disabilitiesmentioning
confidence: 95%
“…(4) Estudos realizados atualmente evidenciam uma ligação entre a HO e o risco do desenvolvimento de doenças cardiovasculares em adultos de meia-idade e idosos. (6) Quando diagnosticada, a HO crônica é tratada gradualmente com intervenções não-farmacológi-cas, como a retirada de medicamentos hipotensores. Caso tais intervenções não sejam suficientes, e o paciente continue sintomático, poderão ser utilizados agentes farmacoterapêuticos.…”
Section: Resultsunclassified
“…(1)(2)(3)(4)(5)(6)(7) Quando o corpo altera sua postura de deitado (em decúbito) para de pé (ereto), alterações hemodinâmicas ocorrem devido à ação da gravidade no sangue, ocasionando a redução da frequência cardíaca e da pressão arterial. Entretanto, o mecanismo humano compensatório, composto pelos barorreceptores, é tão bem desenvolvido, que em indivíduos normais não são percebidos os efeitos dessa queda pressórica na troca de postura.…”
unclassified
“…A study of ambulatory BP monitoring showed that an abnormal diurnal BP of decline of average BP by ≥20% during sleep ("extreme dipping") or rise in nocturnal BP ("reverse dipper") are associated with new occurrence of silent and clinical cerebral ischemia [9]. Orthostatic hypotension is also associated with higher stroke risk [10]. Secondary analyses of a comparative trial of BP regimen suggests that the differences in visit-to-visit variability among the drug regimen accounts for the differences in cardiovascular events better than mean BP differences alone [11].…”
Section: Hypertensionmentioning
confidence: 99%